GIS-material for the archaeological project: Sockenmarken 4:1 and others - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
A archaeological survey was performed during autumn 2005 within a local planning area in the outskirts of Ljungsbro. No finds or features of archaeological interest were found.

Purpose:

The information in the purpose is translated from the archaeological report:
The aim of the survey was to investigate whether the development area contained any archaeological remains. If so, areas with no archaeological remains are to be presented for the developer.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
En arkeologisk utredning etapp 2 utfördes under hösten 2005 inom ett detaljplaneområde i Ljungsbros utkant. Inga arkeologiskt intressanta fynd eller anläggningar noterades. Endast enstaka, recenta föremål påträffades.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med en arkeologisk utredning etapp 2 är att undersöka om det inom misstänkta fornlämningsområden finns fornlämningar eller inte. Om det finns fornlämningar ska om möjligt fornlämningsfria delar kunna anvisas för exploateringen.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Sockenmarken 4:1 m fl
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive